Susceptibility-Guided Therapy vs. Bismuth-Containing Quadruple Therapy as the First-Line Treatment for Helicobacter pylori Infection: A Systematic Review and Meta-Analysis - Ouyang, Yaobin; Zhang, Wenjing; He, Chen; Zhu, Yin; Lu, Nonghua; Hu, Yi (Frontiers in Medicine, 2022)
Background The increased antibiotic resistance of Helicobacter pylori (H. pylori) has led to the decreased efficacy of H. pylori regimens. Aim To evaluate the efficacy, safety, and compliance of susceptibility-guided therapy (SGT) vs. bismuth-containing quadruple therapy (BQT) as the first-line treatment for H. pylori infection. Materials and Methods This meta-analysis was performed in accordance with the PRISMA 2009 guidelines. A systematic search in PubMed, Embase, and Cochrane databases was conducted using the combination of “H. pylori or H. pylori or Hp,” “bismuth quadruple,” and “tailored eradication OR tailored therapy OR susceptibility-guided therapy OR personalized therapy OR antibiotic susceptibility testing.” Results Five studies with 2,110 H. pylori-infected patients were enrolled. The pooled eradication rates of SGT and BQT were 86 vs. 78% (p < 0.05) and 92 vs. 86% (p > 0.05) by intention-to-treat (ITT) and per-protocol (PP) analyses, respectively. SGT has a significantly superior efficacy than BQT [pooled risk ratio (RR) = 1.14, p < 0.05] in a subgroup of cultures with the susceptibility test. The pooled side effect rate was 20% in SGT and 22% in BQT, which showed no significant difference (p > 0.05). The compliances of SGT and BQT were 95 and 92%, respectively. Conclusion Compared with BQT, SGT showed a higher efficacy and similar safety as the first-line treatment of H. pylori infection in areas with high antibiotic resistance. The decision-making of first-line regimens for H. pylori infection should depend on the availability and cost-effectiveness of susceptibility tests and bismuth in local areas.